Combination of 2D-Electrical Resistivity Imaging and Seismic Refraction Tomography methods for groundwater potential assessments: A case study of Khammouane province, Laos - Xayavong, Viengthong; Vu Duc, Minh; Singsoupho, Sounthone; Nguyen Anh, Duong; K.N.D., Prasad; Vu Minh, Tuan; Do Anh, Chung (Vietnam Journal of Earth Sciences, 2023)
2D Electrical Resistivity Imaging (2D-ERI) and Seismic Refraction Tomography (SRT) are non-destructive techniques widely used for numerous geophysical investigations, namely, structural geology mapping, archaeological, engineering, and groundwater investigations. The present study aims to define potential groundwater zones in the Thakhek district of Khammouane Province, Laos, by 2D-ERI and SRT methods; due to the limitation of groundwater potential information, monitoring and evaluation activities regarding groundwater quantity and quality have not been conducted in this study area. The 2D-ERI measurement is based on the Wenner configuration with an electrode spacing of 10-160 m. In contrast, SRT uses a 6.5 kg sledgehammer for a seismic source with a 4 m geophone interval. The results indicate moderate resistivity values ranging from 18.8-71 Ohm-m, and seismic velocities ranging from 1220-2140 m/s were found at 12-30 m in the study region, illustrating the existence of a groundwater/aquifer at this depth. These results correlate well with drilling results from the borehole measurements in the Thakhek district, where the water levels were found at a depth of 12 m for borehole 1 and 15 m for borehole 2. The present study also demonstrates the correlation between 2D-ERI and SRT techniques. The adopted methods favor groundwater identification in the study region and other areas with similar geology formations.